The effect of assests write on the firm’s performance / Min-Tsung Cheng - Cheng, Min-Tsung (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study uses empirical evidence to determine if management recognition asset write-offs improves firm performance. The examination focuses on take-a-bath and information content strategies. The available research on management write-offs behavior presents conflicting results, some of which are interesting. First, for samples positioned at the 1%, 10%, 20%, 90% and 99% quantile level of firm performance ranking, a number of write-offs was found to positively affect the firm’s future performance, supporting the information content hypothesis. However, least squares estimates indicated a negative relationship. Second, under the least squares approach, firm performance was improved in the period following the write-offs at various quantiles, both of which support the take-a-bath hypothesis. Third, testing the equality of individual points can ensure the requisites for quantile analysis and most two-by-two matching coefficients had significant odds.